2020
DOI: 10.1103/physrevmaterials.4.013801
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale imaging of the full strain tensor of specific dislocations extracted from a bulk sample

Abstract: Lattice defects play a key role in determining the properties of crystalline materials. Probing the 3D lattice strains that govern their interactions remains a challenge. Bragg Coherent Diffraction Imaging (BCDI) allows strain to be measured with nano-scale 3D resolution. However, it is currently limited to materials that form micro-crystals. Here we introduce a new technique that allows the manufacture of BCDI samples from bulk materials. Using tungsten as an example, we show that focussed ion beam (FIB) mach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 126 publications
(162 reference statements)
4
73
0
Order By: Relevance
“…The strain sensitivity is of the order of~2 × 10 −4 due to the strong sensitivity of X-rays to the crystal lattice spacing. Such a strain sensitivity is nowadays routinely achieved using BraggCDI methods as reported by [28][29][30][31] . It is most pronounced at edges {110} and corner sites {111}, in the case of the gold cube.…”
Section: Resultsmentioning
confidence: 99%
“…The strain sensitivity is of the order of~2 × 10 −4 due to the strong sensitivity of X-rays to the crystal lattice spacing. Such a strain sensitivity is nowadays routinely achieved using BraggCDI methods as reported by [28][29][30][31] . It is most pronounced at edges {110} and corner sites {111}, in the case of the gold cube.…”
Section: Resultsmentioning
confidence: 99%
“…Hofmann et al report on monochromatic Bragg coherent diffraction imaging (BCDI) to characterize dislocations in Si. [112] The procedure is basically identical to X-ray topography, but now on a nanoscale. As additional results not only the Burger vectors, but also the signs can be identified and-the most innovativethe full 3D strain tensor of individual dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…8, where slices are taken at the center of each of the 3D reconstructions. Each slice depicts the different crystal strain components " ij of the strain tensor (Hofmann et al, 2020). The reconstructed slices show in general the presence of small strain fields inside the crystal on the order of 10 À4 , except in the case of the " yy component, for which the bottom part of the Au particle reaches values up to 8 Â 10 À4 .…”
Section: Calculation Of the Strain Tensormentioning
confidence: 99%
“…For well faceted nanocrystals and when either the Miller indices of a measured reflection or the growth direction of the crystals is known in advance, it is shown that the orientation can be inferred by spinning the crystal until multiple reflections light up and indexing the pole figure using texture analysis algorithms (Richard et al, 2018). Other strategies for collecting multi-reflection BCDI data include obtaining important information about the crystallographic orientation of an isolated specimen before a BCDI experiment from other techniques, either scanning extensive volumes of reciprocal space until a reflection is found or by performing Laue diffraction beforehand at a different instrument (Newton et al, 2009;Hofmann et al, 2017Hofmann et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%